THE PERSPECTIVES OF EDUCATION: COMPETENCES, INTELLECTUAL ENVIRONMENTS, TRANSDISCIPLINARITY - Andrey L. Andreev (Moscow Polytechnic University, 2016)
The article analyses the experience in application of competence approach in Russian education. This approach is compared with the other points of view, especially withthe traditional orientation of education towards knowledge and qualification. The author points out that the competence approach has not improved the quality of education in Russia. Moreover, taken as a kind of universal paradigm, it often hinders the upgrading of real competences. The reason is seen in the fact that to reduce the aims of education to "competences" means to ignore intuitive, or soGcalled personal knowledge, which cannot betested in a usual way. The article also attracts attention to the fact that in newly adoptededucation standards competences are treated as widely as to include moral dispositions and values, and this position from the philosophical point of view seems very doubtful, as soon as in this case the notion of competence embraces nearly the whole contents of our mentality. Instead, the author suggests some alternatives. Taking as a starting point the core trends of modern science (post-non-classical science, technoscience) he promotes key aims for educationsuch as development of transdisciplinary thinking and cultivating of human creativity.